Fast gait speed and self-perceived balance as valid predictors and discriminators of independent community walking at 6 months post-stroke – a preliminary study - Rosa, Marlene (2014)
To determine the validity of walking speed, muscle strength, function of the hemiparetic lower limb and self-perceived balance to predict and discriminate independent community walkers (ICW) within the first 6 months post-stroke.